2022
DOI: 10.3389/fmicb.2022.973257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antibiotic resistance profiles of invasive Haemophilus influenzae from Norway 2017–2021

Abstract: Invasive Haemophilus influenzae (Hi) disease has decreased in countries that included Hi type b (Hib) vaccination in their childhood immunization programs in the 1990s. Non-typeable (NT) and non-b strains are now the leading causes of invasive Hi disease in Europe, with most cases reported in young children and the elderly. Concerningly, no vaccines toward such strains are available and beta-lactam resistance is increasing. We describe the epidemiology of invasive Hi disease reported to the Norwegian Surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Because resistance remains dynamic, further surveillance is warranted to monitor Hi piperacillin/tazobactam resistance development in the future. Our own previous studies 33 and data from other countries 34 , 35 have shown that ampicillin resistance was common and had an increasing trend. 1 However, reduced susceptibility to drugs used for the treatment of invasive Hi infections is still rare.…”
Section: Discussionmentioning
confidence: 83%
“…Because resistance remains dynamic, further surveillance is warranted to monitor Hi piperacillin/tazobactam resistance development in the future. Our own previous studies 33 and data from other countries 34 , 35 have shown that ampicillin resistance was common and had an increasing trend. 1 However, reduced susceptibility to drugs used for the treatment of invasive Hi infections is still rare.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, one out of three BLNAR isolates belonged to ST12 or ST14, clones associated with β-lactam resistance by alteration in PBP3. The ST14 clonal group appears to be endemic in Scandinavia and caused an outbreak of respiratory tract infections in a nursing home in southern Sweden [ 32 , 33 ]. In our study, we did not observe outbreaks caused by ST14.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequencing of 247 invasive Hi cases in Norway between 2017 and 2021 revealed that 170 were NTHi (71.8%). [ 41 ] Among the capsular types, 30 (43.5 %) were Hif, 18 (26.1 %) were Hib, and 15 (21.7 %) were Hia. This study found that the prevalence of NTHi in healthy Chinese children was 13%.…”
Section: Discussionmentioning
confidence: 99%